GAIRAIGO PADA LANSKAP LINGUISTIK DI PULAU ISHIGAKIJIMA, JEPANG - Gracia Agustina; Rani Arfianty; Naufal Hakim (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2025)
Gairaigo as foreign loanwords, have become increasingly prominent in Japan’s public spaces and reflect the interaction between global and local languages ad cultures. This study aims to analyze the forms, functions, and factors undelying the use of gairaigo on Ishigakijima Island, Ishigaki City. Data were collected using a qualitative method through observations of public signage and were analyzed based on the theoretical frameworks of linguistic landscape and sociolinguistics. The results indicate that some gairago have undergone shifts in pronunciation and word choice, although their functions and meanings without change. The adoption of gairaigo in this region is driven by three main factors: 1) the nuanced meanings of foreign words cannot be fully replaced by Japanese equivalents, (2) effectiveness and efficiency in conveying information, and (3) aesthetic value, which is perceived as more appealing and in harmony with the Japanese linguistic sensibility. These findings confirm that gairaigo function not only as a form of linguistic adaptation but also as a cultural integration that enriches public communication in Japan.